2008
DOI: 10.1053/j.jepm.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Gastric Trichobezoar in a Peruvian Guinea Pig (Cavia aperea porcellus)

Abstract: Successful treatment of a gastric trichobezoar in a guinea pig

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…15 Trichobezoars are an uncommon cause of stasis in guinea pigs but also require surgical intervention. 16 Laboratory studies (complete blood cell count, biochemistry, and urinalysis) can be helpful for determination of an underlying cause of anorexia, but most have only nonspecific findings of dehydration or possibly elevated hepatic enzymes from developing hepatic lipidosis. 17 Routine GI stasis is treated with comprehensive supportive care (aggressive fluid hydration, pain management, and assisted nutrition) best performed in a hospital setting for close monitoring.…”
mentioning
confidence: 99%
“…15 Trichobezoars are an uncommon cause of stasis in guinea pigs but also require surgical intervention. 16 Laboratory studies (complete blood cell count, biochemistry, and urinalysis) can be helpful for determination of an underlying cause of anorexia, but most have only nonspecific findings of dehydration or possibly elevated hepatic enzymes from developing hepatic lipidosis. 17 Routine GI stasis is treated with comprehensive supportive care (aggressive fluid hydration, pain management, and assisted nutrition) best performed in a hospital setting for close monitoring.…”
mentioning
confidence: 99%
“…Other reasons for the occurrence of trichobezoars include decreased gastro intestinal motility due to stress factors such as malnutrition, lack of free movement and lack of exercise. These are all assumed to lead to anorexia, dehydration and the accumulation of hair and ingesta in the stomach, which prevents adequate gastric emptying (Theus et al, 2008;Ravi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research has reported increased amylase enzyme activity when Lactobacillus is added to piglets diets [14], and increased sucrase and lactase activity when Lactobacillus is added to pig diets [7]. Bacillus amyloliquefaciens, which has been used as a probiotic in animal feed, produces extracellular enzymes such as amylase, cellulase, proteases and metalloproteases, which can improve nutrient digestion [34]. It has also been reported that probiotic consumption increases the height of intestinal villi in rabbits, increasing the area of nutrient absorption [35].…”
Section: Productive Behaviourmentioning
confidence: 99%
“…In guinea pigs that received probiotics as dietary additives, increases in the population of Lactobacillus and Bifidobacteria decreases in the population of E. coli [32] and decreases in the population of Clostridium spp. [34] were reported. The bacteria L. reuteri, B. subtillis and B.…”
Section: Modification Of the Microbiota And The Environment Of The Di...mentioning
confidence: 99%